PENENTUAN HARGA JUAL DENGAN MENGGUNAKAN PENDEKATAN COST PLUS - Retnosari, Retnosari (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
This study aims to determine the selling price on the production of raffia and straw. The study authors used cost plus method, as cost plus method is considered appropriate in determining the selling price. The research was conducted in the CV. Sumber Cahaya Abadi district. Karanganyar. Method of data collection conducted by the authors using the method of observation, interviews, documentation, and literature. Data analysis is to calculate the selling price and cost plus methods.             Results of research conducted at the CV. Sumber Cahaya Abadi shows that the selling price and profit generated different. Based on this, it is important that the calculation of the sale price to cost plus method to determine the selling price will be on the market that can achieve the desired profit. Keyword: selling price cost plus method.